Metabolic Syndrome In Psoriasis Vulgaris Patient - Wulan Yuwita; Hendra Gunawan; Unwati Sugiri; Dendi Sandiono (Faculty of Medicine, Universitas Airlangga, 2016)
Background: The management of metabolic syndrome in psoriasis vulgaris is rather complicated, including lifestyle modification, diet intake intervention, increasing daily activities, and managing the comorbidity factors. Purpose: Management of metabolic syndrome in psoriasis vulgaris requires holistic approach. Case: A case of metabolic syndrome with psoriasis vulgaris in a-56-year-old woman was reported with chief complaint generalized erythematous plaques, papules, scales, and hyperpigmented macules. Blood pressure was 160/90 mmHg with central obesity and waist circumference was 98 centimeters. The patient manifested with onychodystrophy and subungual hyperkeratosis digiti I pedis bilateral. Fasting blood glucose was 119 mg/dL, and triglyceride was 185 mg/dL. Management: Patient management included methotrexate, bisoprolol, captopril, simvastatin, lifestyle modification, and diabetic diet (1300 kkal and protein 0.8 mg/kg/body weight/day). Conclusion: Holistic management revealed a good response in this case. The initial psoriasis area and severity index (PASI) score before therapy was 24.8, became 9.0 after therapy on day 155th of observation.